Sulforaphane Effects on Cognition and Symptoms in First and Early Episode Schizophrenia: A Randomized Double-Blind Trial. Issue 1 (7th March 2022) - Hei, Gangrui; Smith, Robert C; Li, Ranran; Ou, Jianjun; Song, Xueqing; Zheng, Yingjun; He, Yiqun; Arriaza, Jen; Fahey, Jed W; Cornblatt, Brian; Kang, Dongyu; Yang, Ye; et al.
Abstract: Objective: Cognitive symptoms are associated with significant dysfunction in schizophrenia. Oxidative stress and inflammation involving histone deacetylase (HDAC) have been implicated in the pathophysiology of schizophrenia. Sulforaphane has antioxidant properties and is an HDAC inhibitor. The objective of this study was to determine the efficacy of sulforaphane on cognition dysfunction for patients with schizophrenia. Methods: This double-blind randomized 22-week trial of patients with first-episode schizophrenia was conducted in four psychiatric institutions in China. Patients were randomized to three groups (two doses of sulforaphane vs. placebo) and symptomatic and cognitive assessments were completed at multiple times. The primary outcome measure was change in the MATRICS Composite score. The secondary outcomes were change in MATRICS Domain scores, PANSS Total Scores and change in side-effects. Results: A total of 172 patients were randomized and 151 patients had at least one follow up evaluation. There were no significant effects of sulforaphane, on the primary outcome, MATRICS overall composite score. However, on secondary outcomes, sulforaphane did significantly improve performance scores on MATRICS battery Domains of spatial working memory ( F = 5.68, P = 0.004), reasoning-problem solving ( F = 2.82, P = 0.063), and verbal learning ( F = 3.56, P = 0.031). There were no effects on PANSS symptom scores. Sulforaphane was well tolerated. Conclusion: Although the primary outcome was not significant, improvement in three domains of the MATRICS battery, suggests a positive cognitive effect on some cognitive functions, which warrants further clinical trials to further assess whether sulforaphane may be a useful adjunct for treating some types of cognitive deficits in schizophrenia.